Decentralised spacecraft manoeuvre planning. Issue 5 (19th August 2014) - Cheng, Haoyang; Page, John; Olsen, John; Kinkaid, Nathan
Abstract : Purpose: This paper aims to investigate the decentralised strategy to coordinate the reconfiguration of multiple spacecraft. Design/methodology/approach: The system of interest consists of multiple spacecraft with independent subsystem dynamics and local constraints, but is linked through their coupling constraints. The proposed method decomposes the centralised problem into smaller subproblems. It minimizes the fuel consumption of multiple spacecraft performing a reconfiguration manoeuvre through an iterative computation. In particular, each agent optimises its individual cost function using the most recently available local solution for the other agents. Findings: The simulation scenarios include spacecraft formation reconfiguration and close proximity manoeuvres around obstacles were conducted. The simulation results showed the fast convergence of the proposed algorithm, while local and inter-vehicles constraints were maintained. Originality/value: The main advantage of this approach is that it adopts a linear form of the objective function. This allows the local optimisation problem to be formulated as mixed-integer, linear programming problem, most of which can be quickly solved with resort to commercial software.